The Application Of Acquaintance Training To Improve The Social Skills Of Male Schizophrenia Patients With Social Isolation Nursing Problems: Case Report - Utami, Syafiah Ihsan; Rafiyah, Imas; Hidayati, Nur Oktavia (Journal of Multidisciplinary Research, 2025)
Schizophrenia patients, often experience social isolation by withdrawing from the environment and having difficulty interacting. These symptoms make them feel lonely and difficult to build relationships with others. The purpose of this study was to determine the application of introductory exercises to improve socialization skills in schizophrenic male patients with social isolation nursing diagnoses. The study method used is a clinical case study approach conducted on male patients with social isolation nursing diagnoses in the Merak Room, Cisarua Mental Hospital, West Java Province. From the interventions that have been carried out. The intervention applied is an introductory exercise which is carried out gradually according to the procedure. The results of the intervention show that introductory exercises are effective in gradually improving the patient's social skills, as seen from the improvement of verbal and nonverbal communication and active participation in social activities. Therefore, it is recommended that nurses implement acquaintance training as a strategy to improve socialization skills in patients with social isolation.